Análisis e interpretación a los estados financieros del Bazar y Papelería Oriental del cantón Gualaquiza, provincia de Morona Santiago, periodos 2014-2015. - Quichimbo Pucha, Mirian Cristina (2018)
This research work was carried out in order to meet the requirement prior to obtaining the degree in Accounting and Auditing, Public Accountant Auditor (CPA), Universidad Nacional de Loja, Distance Education Unit , in such a way also allows to fulfill the need of an Analysis and Interpretation to the Financial Statements of "Bazar y Papelería Oriental ", likewise the application of Indicators to check the level of Liquidity, Indebtedness and Profitability, in order to determine the real economic-financial situation of the company. In order to comply with the development of the objectives set out in this paper, it was initiated by maintaining a direct dialogue with the accountant, gathering reliable and necessary information to be analyzed, as well as the Horizontal, Vertical and Financial Indicators Financial Analysis with the objective of determining the situation of Liquidity, Indebtedness and Profitability that the company maintains in the analyzed years and finally to elaborate a report of Financial Analysis with the respective results of improvement obtained, the same ones that facilitate the taking of decisions. Once the work of Financial Analysis in the company was completed and the results obtained were applied as a basis and the appropriate recommendations were established, in which the owner is informed to perform a periodic Financial Analysis in order to know the actual Financial Situation and can use the necessary corrective measures to strengthen the weaknesses of the company. In this way, it will be projected that "Bazar y Papelería Oriental" will be able to implement measures to obtain the best decisions that contribute to generate greater profits and achieve the company's objectives.